KESANTUNAN BERBAHASA PERHIMPUNAN MAHASISWA KATOLIK REPUBLIK INDONESIA CABANG PEKANBARU - Ita Br Siadari; Dudung Burhanudin; Mangatur Sinaga (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research lessons about The Politeness Of Language Association Catholic Student Of Republic Indonesia In Pekanbaru. The purposed of this research is analyze the politeness of language Association Catholic Student Of Republic Indonesia In Pekanbaru through the politeness of language maxim’s. The maxim composed by tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim. This research lesson through Leech politeness of language theory, source the research from the speech’s association of republic indonesia catholic student in pekanbaru. The method that use this research is descriptive of qualitative. The techniques of the data collection did with record and observation, then transcript and analyzed.Key Words: The Politeness Of Language, Maxim’s Of The Politeness, Association CatholicStudent Of Republic Indonesia In Pekanbaru